Estrés laboral y su relación con la satisfacción del personal administrativo de Electro Oriente sede Iquitos, 2023 - Flores Amaringo, Tatiana Elizabeth (2023)
The purpose of this research work is to determine the significant relationship that exists between work stress and the satisfaction of the administrative staff of Electro Oriente, Iquitos headquarters, 2023. The quantitative approach, of a descriptive-correlational type and cross-sectional design, was chosen, whose sample population was 30 administrative workers, who represent 100% of the administrative staff of the Regional Public Service Company of Electricity of the East S.A., to which as-signs you the quizzes. The general score shows very strong positive evidence of 0.996** and a sigma (bilateral) of 0.000, for which it is concluded that there is a significant relationship between work stress and job satisfaction of the administrative staff of Electro Oriente headquarters Iquitos, 2023.